(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background: The development of peritumoural edema and contrast enhancement of brain tumour is both thought to be due to breakdown of blood-brain barrier. However, the exact mechanisms by which these phenomena occur are not completely understood. Our purpose was to find association between the volume of peritumoural edema and the degree of contrast enhancement in MRI of diffusely infiltrating astrocytomas. Method: A total of 42 patients with intracranial astrocytomas diagnosed by MRI findings who underwent surgery with histopathology showing diffusely infiltrating astrocytomas were selected from the study population. The volume of peritumoural edema was measured and visual assessment of the degree of contrast enhancement was scored. Result: A highly significant association was found (p<0.001) between the volume of peritumoural edema and the degree of contrast enhancement. Conclusion: These results can be viewed as indirect, radiological evidence that edema production is quantitatively related to the degree of breakdown of the BBB as determined by the gadolinium enhancement. Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 38-44